Challenges in Simultaneous Microstructuring and Hyperdoping of Germanium with Ultrafast Laser - Gnatyuk, Dmytro; Hamed, Sara; Ebrahimzadeh, Masoud; Liu, Hanchen; Vahanissi, Ville; Laukkanen, Pekka; Savin, Hele; Liu, Xiaolong (Wiley, 2026)
Germanium's compatibility with Complementary Metal-Oxide-Semiconductor (CMOS) and strong near-infrared response make it an attractive platform for infrared photonics, but its intrinsic material properties hinder straightforward extension of absorption beyond the band edge. In this perspective, we synthesize recent and new experiments and analyses on femtosecond-laser approaches that attempt to combine surface microstructuring and hyperdoping of Ge in a single step. We argue that, unlike silicon, Ge's high optical absorption at visible/green wavelengths, shallow energy deposition, lower melting point, and reduced thermal conductivity favor intense localized heating, evaporation, and redeposition-conditions that both produce high baseline sub-bandgap absorption from damage and prevent effective incorporation of thin-film dopant precursors. In a case example, Ti shows only trace incorporation from qualitative measurements. We discuss why laser-induced structural disorder, rather than stable deep dopant incorporation, dominates the optical response, and we outline practical pathways forward: exploring longer wavelengths or gas-phase chemistries, applying separate in situ heating, or decoupling texturing from heavy doping.